Structural analysis of embryogenesis of Leiarius marmoratus (Siluriformes: Pimelodidae) - Oliveira-Almeida, Isângela Rodrigues [UNESP]; Buzollo, Hellen [UNESP]; Costa, Raphael da Silva [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP]; Porto-Foresti, Fábio [UNESP]; Ninhaus-Silveira, Alexandre [UNESP] (Cambridge University Press, 2015)
Embryological studies in fish species are useful to the understanding of their biology and systematics. The available biological data in Leiarius marmoratus are scarce and additional information about its reproductive biology is needed, mainly because this species has been commercially exploited and used in production of hybrid lineages. In order to evaluate the temporal-morphological embryonic modifications in L. marmoratus, samples of nearly 200 embryos were collected at random at different stages of development, starting from fecundation (time zero). Embryos were fixed in modified Karnovsk's solution and 2.5% glutaraldehyde, processed and analysed under optic and electron microscopy. The incubation period of L. marmoratus was equal to 14.42 h at a mean temperature of 28.3 ± 0.07°C. The following stages of embryonic development were established: zygote, cleavage, gastrula, organogenesis and hatching. These stages were divided into phases, as follows: cleavage - phases of 2, 4, 8, 16, 32 and 64 cells and morula; gastrula - phases of 25, 50, 75 and 90% of epiboly and blastopore closure; and organogenesis - neurula, segmentation and pre-larval phases. The embryogenesis of L. marmoratus was typical of neotropical teleosteans, with peculiarities in species development.
Keywords: Embryology; Morphology; Neotropical fish; Ontogenesis; Siluriform; Ultrastructure